We were never here : a novel - Bartz, Andrea (New York : Ballantine Books, 2021)
"An annual backpacking trip has deadly consequences in a chilling new novel from the bestselling author of The Lost Night and The Herd. Emily is having the time of her life--she's in the mountains of Chile with her best friend, Kristen, on their annual reunion trip, and the women are feeling closer than ever. But on the last night of their trip, Emily enters their hotel suite to find blood and broken glass on the floor. Kristen says the cute backpacker she'd been flirting with attacked her, and she had no choice but to kill him in self-defense. Even more shocking: The scene is horrifyingly similar to last year's trip, when another backpacker wound up dead. Emily can't believe it's happened again--can lightning really strike twice? Back home in Wisconsin, Emily struggles to bury her trauma, diving head-first into a new relationship and throwing herself into work. But when Kristen shows up for a surprise visit, Emily is forced to to confront their violent past. The more Kristen tries to keep Emily close, the more Emily questions her friend's motives. As Emily feels the walls closing in on their coverups, she must reckon with the truth about her closest friend. Can she outrun the secrets she shares with Kristen, or will they destroy her relationship, her freedom--even her life?"--
"Reese's book club." -- cover
Keywords: Backpacking -- Fiction; Female friendship -- Fiction; Homicide -- Fiction; Suspense fiction; Thrillers (Fiction); Novels